Pengaruh Konsentrasi Minyak Kelapa Murni (Virgin Coconut Oil) dan Minyak Jarak (Castor Oil) terhadap Sifat Fisikokimia dan Organoleptik Sabun Mandi Cair - Asri Widyasanti; Shayana Junita; Sarifah Nurjanah (Agricultural Faculty, 2017)
VCO contains of lauric acid that perform to smooth and to moisturize the skin. Castor oil has ricinoleic acid that serves to protect the skin. Therefore, both of the oil are suitable to be the raw material for liquid soap making. This study aimed were to produce a liquid soap, to determine the exact concentration of VCO and castor oil for liquid soap and to find out the effect of VCO and Castor Oil concentrations to the characteristics of liquid soap. The method used was laboratory experimental method with descriptive analysis. The treatments in this study were A =concentrations of VCO 100 %, B = concentrations of VCO 80 % and castor oil 20 %, C = concentrations of VCO 50 % and castor oil 50 %, D = concentrations of VCO 20 % and castor oil 80 %, and E = concentrations of castor oil 100 %, from 200 gram soap base. The parameter observed for liquid soap included chemical properties, physical properties of soap, and organoleptic test. The result shows that all treatments complies the requirement SNI 06-4085-1996. The formula of liquid soap with treatment B was revealed as the best product with 0.01 % of total alkali content, pH value of 9.16 , specific gravity 1.06, and total plate count 5colonies/g. This technology process of natural liquid soap production with the VCO and castor oil could be develop and apply in industrial scale.